2012
DOI: 10.1155/2012/296368
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Insulin in Human Breast Milk in Mothers with Type 1 and Type 2 Diabetes Mellitus

Abstract: Despite the important role that insulin plays in the human body, very little is known about its presence in human milk. Levels rapidly decrease during the first few days of lactation and then, unlike other serum proteins of similar size, achieve comparable levels to those in serum. Despite this, current guides for medical treatment suggest that insulin does not pass into milk, raising the question of where the insulin in milk originates. Five mothers without diabetes, 4 mothers with type 1, and 5 mothers with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 37 publications
6
57
0
1
Order By: Relevance
“…Previous findings on the relationship of maternal BMI to milk insulin have been mixed. Our results are consistent with several other studies reporting a positive correlation with maternal pregnancy BMI . In contrast, Shehadeh et al reported postpartum maternal BMI (measured at the time of breast milk sample collection) to have no influence on insulin concentration in transitional milk (days 3 and 10).…”
Section: Discussionsupporting
confidence: 92%
“…Previous findings on the relationship of maternal BMI to milk insulin have been mixed. Our results are consistent with several other studies reporting a positive correlation with maternal pregnancy BMI . In contrast, Shehadeh et al reported postpartum maternal BMI (measured at the time of breast milk sample collection) to have no influence on insulin concentration in transitional milk (days 3 and 10).…”
Section: Discussionsupporting
confidence: 92%
“…The mean milk insulin concentration of 16.7 mU/l was similar to reported milk insulin levels of about 15.64 ± 1.03 mU/l [20]. The mean adiponectin concentration of 35.0 ng/ml was slightly higher than previously reported milk concentrations at 1 year of lactation of 25.7 ± 1.4 ng/ml [21].…”
Section: Resultssupporting
confidence: 81%
“…The insulin concentration in early milk does not appear to be affected by the mother's gestational diabetes status. While the insulin concentration in mature milk of nondiabetic women is not different from that of women with GDM (Ley et al 2012), maternal prenatal metabolic indicators, such as BMI, fasting glucose, insulin resistance, insulin sensitivity, and adiponectin levels, can predict insulin concentration in mature milk (Ley et al 2012;Whitmore et al 2012).…”
Section: Feedingmentioning
confidence: 96%